UZBEKISTAN IS DEVELOPING PILGRIMAGE TOURISM FACILITIES. (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
Abstract: This article Uzbekistan is actively developing its pilgrimage tourism facilities, leveraging its rich cultural and historical heritage. As one of the key centers of Islamic civilization, Uzbekistan hosts numerous sacred sites, mosques, mausoleums, and madrasas that attract both local and international pilgrims.